Accreditation of National Polio Laboratory by World Health Organization - Etem ÖZKAYA (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2003)
In the frame of World Health Organization (WHO) Programme for Eradication of Poliomyelitis (PEP), Virology, Tissue Culture and Enteroviruses Laboratory of Refik Saydam Central Institute of Hygiene has been giving service as “National Laboratory” in this programme and one of the major task of which is to isolate polioviruses from feacal samples of the patients diagnosed as acute flask paralysis (AFP). In the frame of the PEP, WHO has started to accredite all National Polio Laboratories for providing undercontrol and healthy laboratory analysis in European region since 1997. Accreditation provides documentation that the laboratory has the capability and the capacity to detect, identify, and promptly report wild polioviruses that may be present in clinical and environmental specimens. Accreditation of Poliovirus Laboratories is reviewed annually by the WHO Regional Office and is based on laboratory performance during the immediately preceding 12 months with complete data. Tissue Culture and Enteroviruses Laboratory which has been giving service as National Laboratory is accredited fully on February 2002 by WHO.